Complexity of finding Pareto-efficient allocations of highest welfare - Biró, Péter,Gudmundsson, Jens (Institute of Economics, Centre for Economic and Regional Studies, 2020)
We allocate objects to agents as exemplified primarily by school choice. Welfare judgments of the object-allocating agency are encoded as edge weights in the acceptability graph. The welfare of an allocation is the sum of its edge weights. We introduce the constrained welfare-maximizing solution, which is the allocation of highest welfare among the Pareto-efficient allocations. We identify conditions under which this solution is easily determined from a computational point of view. For the unrestricted case, we formulate an integer program and find this to be viable in practice as it quickly solves a real-world instance of kindergarten allocation and large-scale simulated instances. Incentives to report preferences truthfully are discussed briefly.
10419/222085
Keywords: Graue Literatur; Assignment; Pareto-efficiency; Welfare-maximization; Complexity; Integer programming